Answer:
Step-by-step explanation:
x-1=5
2x=5+1
2x=6
2/2=6/2
X=3
|2x-1|=-5
2x=5+1
2x=-4
2/2=-4/2
x=-2
so (x=3 and -2)
Step-by-step explanation:
As < A and < B are vertical angles so
<A = < B
5x + 12 = 6x - 11
6x - 5x = 12 + 11
x = 23
Hope it will help :)❤
40 x 0.08875 = 3.55
40 + 3.55 = 43.55
the sum is $43.55
Answer:
multiplying both-side of the equation by 3
substituting 36 for p to check the solution
Step-by-step explanation:
To solve the equation p/3 = 12, we will follow the steps below;
first multiply 3 to both-side of the equation, that is:
p/3 × 3 = 12 × 3
On the left-hand side of the equation, 3 at the numerator will cancel-out 3 at the denominator, leaving us with just p while on the right-hand side of the equation 12 will be multiplied by 3
p= 36
To check the correctness of the equation, we can substitute p = 36 back into the equation and then check, that is;
p/3 = 12
36/3 = 12
This implies p = 36 is correct